Details of a prospective protocol for a collaborative meta-analysis of individual participant data from all randomized trials of intravenous rt-PA vs. control: statistical analysis plan for the Stroke Thrombolysis Trialists' Collaborative meta-analysis. - Stroke Thrombolysis Trialists' Collaborative Group (2013)
RATIONALE: Thrombolysis with intravenous alteplase is both effective and safe when administered to particular types of patient within 4·5 hours of having an ischemic stroke. However, the extent to which effects might vary in different types of patient is uncertain. AIMS AND DESIGN: We describe the protocol for an updated individual patient data meta-analysis of trials of intravenous alteplase, including results from the recently reported third International Stroke Trial, in which a wide range of patients enrolled up to six-hours after stroke onset were randomized to alteplase vs. control. STUDY OUTCOMES: This protocol will specify the primary outcome for efficacy, specified prior to knowledge of the results from the third International Stroke Trial, as the proportion of patients having a 'favorable' stroke outcome, defined by modified Rankin Score 0-1 at final follow-up at three- to six-months. The primary analysis will be to estimate the extent to which the known benefit of alteplase on modified Rankin Score 0-1 diminishes with treatment delay, and the extent to which it is independently modified by age and stroke severity. Key secondary outcomes include effect of alteplase on death within 90 days; analyses of modified Rankin Score using ordinal, rather than dichotomous, methods; and effects of alteplase on symptomatic intracranial hemorrhage, fatal intracranial hemorrhage, symptomatic ischemic brain edema and early edema, effacement and/or midline shift. DISCUSSION: This collaborative meta-analysis of individual participant data from all randomized trials of intravenous alteplase vs. control will demonstrate how the known benefits of alteplase on ischemic stroke outcome vary across different types of patient.